Estudio de factibilidad para la creación del centro de acompañamiento académico “La Nave Maestra” en los niños del cantón La Maná, año 2023. - Cunuhay Changoluiza, Lidia Leticia (2023)
The present research had as general objective, to develop a feasibility study for the creation of the academic accompaniment center "La Nave Maestra", in order to achieve the proposed objectives it was necessary to collect primary information through field research, by using the survey technique directed to the owners of the existing academic support centers and the legal representatives of the students up to the basic average. The research had a quantitative approach and a descriptive level, with regard to the methodology, the logical and deductive historical methods were used. The results obtained revealed the existence of a current offer of 7.680 hours per year and an unsatisfied demand of 445.317,12 hours, evidencing a wide market for the proposal, around which it was projected to capture 2% equivalent to 10,368 hours per year. Through the technical study, the location was determined, in a macro, meso and micro way, as well as the flow charts of the service, the infrastructure distribution, and the organizational structure. The total investment required was $51,744.04, from which 8% ($980.29) will be financed with own capital and 92% ($11,000) by a 24-month loan. The net profit to be obtained for the first year was $10.950,48 with an IRR of 28%, a C/B ratio of $1,56 and a PRI of 2 years, 2 months and 8 days; For this reason, it is vitally important to recommend the creation of an academic monitoring center that benefits the social and economic sphere of the canton La Maná.